PI3K/AKT/MTOR and ERK1/2-MAPK signaling pathways are involved in autophagy stimulation induced by caloric restriction or caloric restriction mimetics in cortical neurons - Ferreira-Marques, Marisa (2021)
Caloric restriction has been shown to robustly ameliorate age-related diseases and to prolong lifespan in several model organisms, and these beneficial effects are dependent on the stimulation of autophagy. Autophagy dysfunction contributes to the accumulation of altered macromolecules, and is a key mechanism of promoting aging and age-related disorders, as neurodegenerative ones. We have previously shown that caloric restriction (CR), and CR mimetics Neuropeptide Y (NPY) and ghrelin, stimulate autophagy in rat cortical neurons, however by unknown molecular mechanisms. Overall, we show that CR, NPY, and ghrelin stimulate autophagy through PI3K/AKT/MTOR inhibition and ERK1/2-MAPK activation. The knowledge of these kinases in autophagy regulation and the contribution to the understanding of molecular mechanism facilitates the discovery of more targeted therapeutic strategies to stimulate autophagy, which is relevant in the context of age-related disorders.